1998
DOI: 10.1148/radiology.206.3.9494507
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion injury of cervical nerve roots: enhanced intradural nerve roots at MR imaging.

Abstract: Although visualization of nerve roots is a problem, enhanced MR imaging is a noninvasive means of obtaining anatomic information and unique physiologic information on injured intradural nerve roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…127 (59,60,63,65,66) reported the accuracy of MRI for patients and nerves; two studies (43,44) reported results only at the patient level; three studies (62,64,67) reported the accuracy with the nerve as the exclusive unit of analysis; and the unit of analysis was unclear in one study (61), so it did not contribute to summary estimates. With the patient as the unit of analysis (43,44,59,60,63,65,66), 104 of 144 patients (median, 72%; IQR: 53%-86%) had at least one root avulsion.…”
Section: Key Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…127 (59,60,63,65,66) reported the accuracy of MRI for patients and nerves; two studies (43,44) reported results only at the patient level; three studies (62,64,67) reported the accuracy with the nerve as the exclusive unit of analysis; and the unit of analysis was unclear in one study (61), so it did not contribute to summary estimates. With the patient as the unit of analysis (43,44,59,60,63,65,66), 104 of 144 patients (median, 72%; IQR: 53%-86%) had at least one root avulsion.…”
Section: Key Resultsmentioning
confidence: 99%
“…With the patient as the unit of analysis (43,44,59,60,63,65,66), 104 of 144 patients (median, 72%; IQR: 53%-86%) had at least one root avulsion. With the nerve as the unit of analysis (59,60,(62)(63)(64)(65)(66)(67), 583 of 918 roots were avulsed (median, 55%; IQR: 38%-71%). The time from injury to MRI was reported in six studies (44,59,60,63,65,66) and varied considerably, with a median delay of 36 days (IQR: 26-66 days; range, 0-840 days).…”
Section: Key Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is caused by simultaneous traction of the arm and lateral flexion of head to the opposite direction, the most common situation to cause such injury being road traffic accident followed by birth injury, fall of heavy object over shoulder and very rarely missile injuries or sharp stab injuries though they are more likely to cause distal plexus injuries. Nerve root avulsions are more commonly accompanied by traumatic pseudomeningocele formation 3 , which can however rarely exist without any nerve root avulsions (Fig 1A, 1B & 1C). Conversely nerve root avulsions can occur without pseudomeningocele formation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The recent advent of multidetector CT scanners enables us to obtain data with high spatial resolution along a spine. 4 However, the large number of thinslice images generated from myelographic CT would make the qualitative and quantitative diagnosis of the injured individual nerve roots a challenging task for radiologists if they evaluated each image one by one.…”
Section: Introductionmentioning
confidence: 99%